The effect of service quality on students’ satisfaction in the University Health Centre at Universiti Utara Malaysia (Research, Society and Development, 2023)
Service quality is an issue that organizations must address particularly service-oriented organizations. This quality will indicate whether the organization achieved the requisite level of quality based on the expectations of the organization and the students. This study is aimed to determining that focus on the effect of service quality on students’ satisfaction in the University Health Centre at Universiti Utara Malaysia. The methodology of this research, design used was a quantitative approach and assessed the five dimensions of service quality (independent variables), which were tangible, reliability, responsiveness, assurance, and empathy. This study employed a cluster sampling technique. The questionnaire was distributed to students of Universiti Utara Malaysia who stayed in Sime Darby Student Residential Hall and 117 students responded to the questionnaire. The SPSS version 29 was used to analyse the data. The findings from the analysis revealed that tangible, reliability, responsiveness, assurance, and empathy were found to record significant effects towards students’ satisfaction. In addition, the responsiveness, assurance, and empathy variables were highly significant in determining students’ satisfaction. Practical and theoretical implications for comprehending the characteristics of the effect of tangible, reliability, responsiveness, assurance, and empathy would make academic and service providers be more concern about students’ satisfaction to improve service quality in the University Health Centre.